DINAMIKA POLITIK ANGGARAN DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI LEMBAGA SEKOLAH - Robiatul Adawiyah; Agustina Damanik (Yayasan Baitul Hikmah al-Zain, 2025)
This study aims to analyze the implications of budget politics on the quality of education in schools. The main problem in this study is how education budget policies are influenced by political dynamics, and to what extent this impacts the quality of education services in schools. This study uses a qualitative approach with a literature study method and in-depth interviews with a number of school principals and education policy makers. The results of the study show that the budgeting process is often influenced by certain political interests which cause budget allocations not always based on the real needs of schools. This has an impact on the lack of educational facilities, limited teacher training, and the low effectiveness of quality improvement programs. The conclusion of this study shows that transparency and accountability in the budget politics process are very important to ensure the quality of sustainable education in schools. A strong political commitment is needed to place education as a national development priority.